Value added mechanism and organisational model optimisation of agricultural products circulation value chain from the perspective of game theory - Peng Fan; Yifeng Wang; Nan Xu (Acta agriculturae Scandinavica. Section B, Soil and plant science, 2021)
In order to promote the coordinated development of various circulation entities and promote the economic benefits of the value chain, this paper firstly analyses the value-added mechanism of agricultural products circulation value chain from five aspects: primary processing creates form utility, cross regional transportation creates location utility, storage supply creates time utility, market division creates acquisition utility and brand creation creates perceptual utility. Secondly, the paper analyses the diversification problems of agricultural products value chain organisations. Finally, based on the perspective of price, subject interest and industry chain operation, three optimisation methods of organisation mode are proposed, which are integrated price monopoly, subject interest coordination and mixed vertical industrial chain operation. The outcome of this effort in the traditional organisation mode is incessantly well-improved, upgraded and promote this implementation to enhance the productivity of agricultural products towards rural circumstances.